PENERAPAN MODEL PEMBELAJARAN PBL TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN GEOGRAFI MAN 1 PONTIANAK - Rhamayansi, Deyya; Astriati, Nuraini; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to determine the differences of student learning outcomes in class that applies PBL learning models and class that applies conventional methods or models in class XI IPS MAN 1 Pontianak. The method used in this research is nonequivalent control group design with quasi-experimental research methods (Quasi Experiment). The sampling technique used in this study was purposive sampling. The result of class that used PBL model is 84.45 and the control class using conventional method obtained an average value of 78.20. Based on the analysis data of those tests, the results show that there are differences of student learning outcomes in class using PBL learning model in Geography Subject especially natural disaster mitigation material using conventional method. This is proven by the statistical analysis of the Independent Sample T-Test in the SPSS 16 program which obtained the Sig. (2-tailed) of 0.001. So, Ho is rejected or Ha is accepted, because the value of Sig. t-test (2-tailed) that is 0.001 <0.05 which means that there are differences of student learning outcomes in class using PBL model in Geography Subject especially natural disaster mitigation material using conventional method.Â Keywords : Problem Based Learning model, Learning Outcomes.